THE ART OF DANCE COMBINATION - CHOREOGRAPHY: नृत्य संयोजन की कला - कोरियोग्राफी - Harmalkar, Suchitra (International Journal of Research -GRANTHAALAYAH, 2015)
Choreography literally means Dance writing It is derived from the Greek word xopeia. The common meaning of choreography is - group structure, and the person, dancer or performer who performs this work is called a choreographer. We do not get any scriptural consensus or information about choreography but today this word is very popular in the context of dance. is . कोरियोग्राफी का शाब्दिक अर्थ है Dance writing यह ग्रीक भाषा के शब्द xopeia से लिया गया है । कोरियोग्राफी का सामान्य अर्थ है- समूह संरचना, और जो व्यक्ति, नर्तक या कलाकार इस कार्य को करता है , उसे कोरियोग्राफर कहा जाता है कोरियोग्राफी के विषय मे कोई शास्त्र सम्मत विधान या जानकारी हमें प्राप्त नहीं होती किन्तु आज नृत्य के संदर्भ में यह शब्द बहुप्रचलित है ।